2010
DOI: 10.1262/jrd.09-184h
|View full text |Cite
|
Sign up to set email alerts
|

The Nucleolus in the Mouse Oocyte is Required for the Early Step of Both Female and Male Pronucleus Organization

Abstract: Abstract. During oocyte growth in the ovary, the nucleolus is mainly responsible for ribosome biogenesis. However, in the fully-grown oocyte, all transcription ceases, including ribosomal RNA synthesis, and the nucleolus adopts a specific monotonous fibrillar morphology without chromatin. The function of this inactive nucleolus in oocytes and embryos is still unknown. We previously reported that the embryo lacking an inactive nucleolus failed to develop past the first few cleavages, indicating the requirement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 18 publications
1
48
0
Order By: Relevance
“…However, as the protein composition of this unique structure is unknown it is also not known to what extent NPBs play an active role in this process. Ogushi and Saitou [19] have demonstrated that zygotic and GV-stage oocyte NPBs are not equivalent in composition and/or function. Exchanging zygotic NPBs for oocyte NPBs in mouse onecell stage embryos lead to a lag in cell cycle progression and severe developmental arrest.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, as the protein composition of this unique structure is unknown it is also not known to what extent NPBs play an active role in this process. Ogushi and Saitou [19] have demonstrated that zygotic and GV-stage oocyte NPBs are not equivalent in composition and/or function. Exchanging zygotic NPBs for oocyte NPBs in mouse onecell stage embryos lead to a lag in cell cycle progression and severe developmental arrest.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting observation was made by Ogushi and Saitou in 2010 [19]. These authors have transplanted the NPBs from GV stage oocytes into different oocyte maturation Fig.…”
Section: Transplanting the Nucleolus Into One Cell Stage Embryosmentioning
confidence: 91%
See 1 more Smart Citation
“…After fertilization, the maternally derived, transcriptionally inactive nucleolus appears in both male and female pronuclei and in the embryonic nuclei until the four-cell or eightcell stage; that is, it is present until EGA (Zatsepina, Baly, Chebrout, & Debey, 2003). Although the nucleolus at this stage appears to be inactive and shows a highly compacted structure, studies with mice have revealed that it is essential for early embryonic development (Ogushi et al, 2008;Ogushi & Saitou, 2010). Embryos originating from enucleolated oocytes arrest between the two-cell and four-cell stages (Ogushi et al, 2008).…”
Section: Nucleolimentioning
confidence: 99%
“…The enucleolation method also showed that nucleoli (NPBs) in zygotes are formed from the original oocyte nucleolar material [11]. Further detailed analysis demonstrated that the presence of nucleoli in pronuclei is absolutely essential for normal embryonic development [12][13][14][15]. As mentioned above, contrary to somatic cells, the composition of NPBs is almost unknown.…”
mentioning
confidence: 96%